The mitochondrial unfolded protein response (UPRmt) protects against osteoarthritis - Zhibin Zhou; Jiajia Lu; Mei Yang; Jiao Cai; Qiang Fu; Jun Ma; Lei Zhu (2022)
The mitochondrial unfolded protein response (UPRmt) is a mitochondrial-to-nuclear signaling pathway that is activated to maintain mitochondrial function when there is an accumulation of misfolded proteins within mitochondria. Mitochondrial function is essential for chondrocyte homeostasis, and mitochondrial dysfunction is a characteristic of osteoarthritis (OA). However, the role of the UPRmt in OA remains unclear. In the present study, the level of the UPRmt was examined in primary mouse chondrocytes subjected to different stresses and in the articular cartilage of OA model mice and OA patients. The relationship between UPRmt activation and OA progression was studied. The UPRmt was induced in primary mouse chondrocytes subjected to diverse stresses and in the cartilage of OA mice. Enhancement of the UPRmt with nicotinamide riboside (NR) significantly improved mitochondrial function, reduced chondrocyte death, attenuated OA pain, and ameliorated OA progression, and the protective effects decreased significantly in chondrocyte-specific Atf5 knockout (ATF5f/fCol2a1-CreERT2) mice. UPRmt induction was also identified in the articular cartilage of OA patients and was associated with reduced chondrocyte death, less severe hip pain, and lower levels of inflammation in synovial fluid. These findings identify the induction of the UPRmt in primary mouse chondrocytes exposed to pathological stresses and in the articular cartilage of OA model mice and OA patients. Enhancement of the UPRmt ameliorates OA progression, suggesting that the UPRmt exerts a protective effect against OA and may be a potential diagnostic and therapeutic strategy for OA.